The beneficial effect of electro acupuncture on obesity may be associated with irisin, nesfatin-I and preptin levels - Ercan, Zubeyde; Deniz, Gulnihal; Caf, Fatma; Algul, Sermin; Gazioglu, Abdullah; Kavakli, Ahmet (Cognizant Communication Corp, 2019)
The action mechanism of acupuncture, one of the alternative methods used in obesity treatment, is unknown. The purpose of this study was to investigate the effect of electroacupuncture on weight loss and whether acupuncture treatment can change circulating levels of irisin, nesfatin-I and preptin, which have been discovered in recent years and plays an important role in nutrition and energy metabolism. Irisin, a newly discovered myokine, is associated with increased energy consumption and has a potential role in obesity. Preptin, present in islet b-cells of pancreas and associated with the carbohydrate metabolism, nesfatin-I is an anorexogenic peptide composed of 82 amino acids and regulates food intake by modulating neuropeptides in feeding centers in the brain. These three new hormones regulate energy intake and expenditure and preserve energy homeostasis and composition. In this study 4 weeks old Sprague Dawley male rats (n=16) were randomly divided into 2 groups which were the control (C): normal diet and obese (O): high fat diet (HFD) groups. After 16 weeks which obesity was developed, electroacupuncture (EA) was performed to rats once in every second days for 3 times weekly for four consecutive weeks. EA was applied bilaterally to Zusanli (ST36), Bai Hui (Du20), He Gu (Li4), Tianshu (ST25) and Sanyinjiao (SP6) acupoints in animals to both groups. Blood was collected before and after EA and serum irisin, nesfatin-I and preptin levels were analyzed by ELISA (Enzyme-InducedImmunosothent Analysis) method. After four week EA treatment, there was sginificant decrease of the average body weight in both groups rats. There were increases in the serum nesfatin-I and preptin levels in the both groups after acupuncture. A decrease was observed in the irisin levels in obese group, but an increase in the control group. These findings suggest that electroacupuncture may help to weight loss due to its effects on some important metabolic hormones such as irisin, nesfatin-I and preptin only for a few weeks. It is thought that the changes of these hormones levels may playa role in beneficial effect of acupuncture used in the treatment of human obesity. The application of EA in the treatment of obesity is very effective, which may have led to weight loss by altering these hormone levels in obese people.
Keywords: Electroacupuncture; Irisin; Nesfatin-I; Obesity; Preptin